+0  
 
+3
34
1
avatar+1672 

Solve each equation and express your answer in simplest radical form:

 

1.) -x^2 + 4x = 13

 

2.) 5x - 7x^2 = 3x + 4 

 Feb 25, 2019
 #1
avatar+17253 
+1

1  -x^2 + 4x = 13

     -x^2+4x-13 = 0        simplify things by multiplying by -1 (not NECCESSARY)  and use Quadratic Formula

  x^2-4x+13 = 0  

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)      a = 1    b = -4   c = 13

                                results in   x = 2+-3i

 

 

You can try the second one...

 

7x^2-2x+4 = 0      Quadratic formula    a = 7   b = -2  c = 4

 Feb 25, 2019

31 Online Users

avatar